Hygienic-sanitary conditions in units producing meals: a review (Research, Society and Development, 2020)
In addition to dietary standards, a Meal Production Unit (UPR) must adjust hygienic standards in order to meet the needs and ensure the integrity of the health of its guests, thus preventing the appearance of outbreaks of Foodborne Diseases. The objective of this study was to carry out an integrative review seeking the classification and adequacy of UPRs, with the purpose of analyzing the strategies used for the management of hygienic-sanitary quality. The search for the articles was based on the analysis of data from scientific publications, in a period from 2012 to 2019. Bringing as results information referring to the classification of hygienic-sanitary conditions in UPRs and their conformity indexes. As already strongly emphasized in the literature and in good practice manuals, food safety is an eminent concern in which there can be no flaws and should always be updated, as in all stages of food processing and handling, there are possibilities of contamination. and with that, possible pathologies.